2005
DOI: 10.1089/hum.2005.16.381
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Dispersion of Adeno-Associated Virus Serotype 1 and Adeno-Associated Virus Serotype 6 Vectors in the Rat Central Nervous System and in Human Glioblastoma Multiforme Xenografts

Abstract: The transduction patterns of recombinant adeno-associated virus serotype 1 (AAV1) and serotype 6 (AAV6) vectors were assessed in human glioblastoma multiforme (GBM) cell lines, in human GBM biopsy spheroids, and in tumor xenografts growing in nude rat brains. All the cell lines tested (A172, D37, GaMg, HF66, and U373Mg) were found to be permissive to both AAV1 and AAV6 vectors, and thus displayed a transduction pattern similar to AAV2 vectors. For every cell line tested, the transduction efficiency displayed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…The vimentin-specific antibody uniformly labels human tumor cells in the GBM spheroid model. 22,25 Lowmagnification images confirmed single-tumor-cell infiltration into the corpus callosum in GBMI lesions (Figure 7a). Central areas in this xenograft stained for vimentin, whereas anti-HSV-1 antibody labeled G207-infected cells (Figure 7b).…”
Section: Infection Of Infiltrative Glioma Cells By G207mentioning
confidence: 68%
See 1 more Smart Citation
“…The vimentin-specific antibody uniformly labels human tumor cells in the GBM spheroid model. 22,25 Lowmagnification images confirmed single-tumor-cell infiltration into the corpus callosum in GBMI lesions (Figure 7a). Central areas in this xenograft stained for vimentin, whereas anti-HSV-1 antibody labeled G207-infected cells (Figure 7b).…”
Section: Infection Of Infiltrative Glioma Cells By G207mentioning
confidence: 68%
“…20 Direct transplantation of such 'organotypic' spheroids into rodent brains forms lesions that eventually recapitulate all the histopathological hallmarks of GBM in situ, such as extensive single-cell infiltration, angiogenesis the occurrence of necroses with palisading tumor cells, endothelial proliferations and dilated, thrombotic vessels. 18,21 We have recently used this model to evaluate gene transfer to human GBM cells 22,23 as well as to study the biological aspects of tumor cell invasion. 24 Since the described model reflects the key features of human glioma progression, we chose to assess the effect of G207 on a set of xenograft phenotypes that follow these biological features.…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen rats were implanted with GBM6 spheroids and used to assess therapeutic effect. Surgery was done as previously described (8). The handling of the animals and the surgical procedures were done in accordance with the Norwegian Animal Act and the local ethical committee approved the protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Staining was done as previously described (8). Negative control slides, containing sections of a xenograft generated from the same patient spheroids without G207 treatment, were routinely included.…”
Section: Methodsmentioning
confidence: 99%
“…More than 100 genotypes of AAV have been identified that fall into nine antigenically different genetic clades (Gao et al, 2004). More than 100 genotypes of AAV have been identified that fall into nine different antigenic genetic clades (Gao et al, 2004;Gao et al, 2005) but only AAV1-10 have been engineered into vectors (Davidson et al, 2000;Gao et al, 2005;Gao et al, 2002;Huszthy et al, 2005;Wang et al, 2005). Production of rAAV has been improved recently and extremely high titer pure virus is commonly obtained (Zolotukhin et al, 2002).…”
Section: Adeno-associated Virusmentioning
confidence: 99%